Reform of the European Union sugar regime : ACP sugar industries under treat - a compilation of speeches and articles (The Ministry GeorgetownGY, 2005)
Presents statements made by the Minister of Foreign Trade and International Cooperation, Guyana, the Hon. Clement J. Rohee and other ACP officials.
Keywords: SUGAR INDUSTRY